2019
DOI: 10.1021/acs.chemrev.9b00204
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticles in Polyols: Synthesis, Catalytic Couplings, and Hydrogenations

Abstract: Alcohols, in particular polyols, are well-known for the synthesis of metal nanoparticles often acting as reducing agents, solvents, and stabilizers. Given not only their structural flexibility depending on the number of OH functions and their inherent H bonding interactions, but also the wide range of polyol molecular weights readily available, different physico-chemical properties (boiling point, polarity, viscosity) could be exploited towards the synthesis of well-defined nanomaterials. In particular, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(127 citation statements)
references
References 268 publications
(639 reference statements)
1
125
1
Order By: Relevance
“…40 Recently, Gómez et al summarized the use of PdNPs for the synthesis of polyols via catalytic coupling and hydrogenation. 41 Dandia et al recently reported the synthesis of three-, ve-, six-and seven-membered ring systems using nanocatalysts. 42 Chaudret et al recently covered the role of several MNPs in s-H-H, s-C-H, and s-Si-H bond activation.…”
Section: Nanocatalysismentioning
confidence: 99%
“…40 Recently, Gómez et al summarized the use of PdNPs for the synthesis of polyols via catalytic coupling and hydrogenation. 41 Dandia et al recently reported the synthesis of three-, ve-, six-and seven-membered ring systems using nanocatalysts. 42 Chaudret et al recently covered the role of several MNPs in s-H-H, s-C-H, and s-Si-H bond activation.…”
Section: Nanocatalysismentioning
confidence: 99%
“…Since heterogeneous catalysis is based on processes taking place at the surface, the use of finely dispersed catalysts is often adopted in order to reduce the amount of material and maximize its catalytic effect [3,4]. For this purpose, palladium nanoparticles are widely used to catalyze organic reactions [5][6][7][8][9][10][11][12][13][14]. Similar to palladium, palladium(II) oxide (PdO) has also found applications in many catalytic processes [15][16][17][18], but few studies were carried out on the production of palladium oxide nanoparticles compared to the wide range of works concerning metallic palladium particles [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Palladium nanoparticle‐based catalysts play a pivotal role in H 2 ‐based reactions, such as hydrodehalogenations of haloarenes and the reduction of unsaturated substrates, including oxidized nitrogen derivatives, especially for the production of anilines at industrial scale . This versatile reactivity offers great potential towards contaminated water/soil remediation via degradation of pollutants and environmentally friendly processes by means of selective catalytic reduction approaches precluding NO x emissions .…”
Section: Introductionmentioning
confidence: 99%